The Role of The Area Business Manager on the Work Motivation of Bancassurance Consultants ( A Case Study at AIA CIMB Niaga) - Dewi Retno Budiastuti; Ratna Kartika Sari (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
BC working for an insurance company, namely AIA Financial, must be able to locate and present themselves at the partner bank where the BC is placed. With all this work, BC often experiences a decline in performance and motivation. So, the task of an Area Business Manager is to monitor and motivate the BCs. The research method used in this research is qualitative research, which was carried out in one of the AIA areas in 5 CIMB Niaga bank branches in Jakarta. The efforts made by ABM to BC so far have been quite successful in motivating BC, as can be seen from BC's active communication and good relations with bank staff so that the referrals provided are active every day. In the first week, BC received data on customers who will be offered AIA products; apart from that, BC is also active in following up on data on customers who have joined AIA to resell. The training carried out by AIA management also had a positive impact on BC's motivation, increasing their ability to know products, sell well, and understand the sales process without incorrect data.